(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The small intestine and its parts have been studied by scientists for hundreds of years. Today, the development of the organ, interaction of its layers, vessels, development of the innervation apparatus, topography, histogenesis and many other issues related to morpho-biochemical changes in this organ have been studied. However, the morpho-functional characteristics of the small intestine have not been sufficiently addressed.